Who do you troll and Why: An investigation into the relationship between the Dark Triad Personalities and online trolling behaviours towards popular and less popular Facebook profiles. (December 2017) - Lopes, Barbara; Yu, Hui
Abstract: This experiment examined the influence of Dark Personalities in trolling behaviour towards popular and less popular Facebook profiles. One-hundred and thirty-five participants were recruited to view two fake Facebook profiles and rate how much they would agree with some trolling comments to each profile, as well as how they perceived themselves in comparison to each profile in terms of social acceptance and rank. In addition, participants completed the Short Dark Personality Questionnaire. Results suggested Psychopathy was positively associated with trolling behaviours while Narcissism was associated with a tendency to see oneself superior to others. Moreover, the higher the Psychopathy score the more likely the participants would troll the popular profile. On the other hand, the higher the Narcissism score the more likely participants were to perceive themselves as superior to the popular profile. These analyses revealed the different influence Dark Personality traits play on different behavioural tendencies. Dynamics among the Dark Personalities in relationship with online behaviours and the implications of the study are discussed. Highlights: Perceived popularity may attract attention and bullying in social media websites. The Dark Personalities predict different behaviours towards popular vs. less popular Facebook profiles. Psychopathy is associated with trolling behaviour and more so of popular Facebook profiles. Narcissism is associated with downward social comparison and more so to popular Facebook profiles.